Survival Analysis for Predicting Bankruptcy in Small and Medium-sized Enterprises (SMEs). - Mena-Siles, David; Gemar-Castillo, Germán (My University, 2024)
This research consists of a predictive analysis of SME insolvency, with the aim of identifying financial measures that can anticipate possible insolvency situations. The work includes a selection of variables that have been little explored in the literature, obtaining unique conclusions. The uniqueness lies in the geographical region of growing business expansion, whose results are generalisable to SMEs in other similar geographical regions. The methodology used will be a survival analysis with the non-parametric Kaplan-Meier estimator and logistic regression with complementary log-log, to detect the influence of each variable. The results determine that the survival of SMEs depends on the financial structure, EBITDA, financial result, profitability of assets, fixed assets, working capital and productivity of human capital. This study has important implications for management control in the business world as an early warning system for insolvency situations and a strategic support tool to prolong survival.
Keywords: Pequeñas y medianas empresas; Quiebra; Reorganización de empresas; Survival; Insolvency; Bankruptcy; Business; Management